Bioatividade de extratos vegetais sobre Ceratitis capitata Wiedemann (Diptera: Tephritidae) - Costa, Natanaelma Silva da (2022)
The fruit fly Ceratitis capitata is considered one of the main pests of fruit growing worldwide and its control is mostly carried out by conventional chemical means, which generates a demand for alternative methods that minimize the environmental impacts of the use of these products. The plant biodiversity of the Caatinga is widely referenced by the potential of its bioactive secondary metabolites on phytophagous insects. In this context, we sought to evaluate the yield and phenolic composition of plant extracts of the botanical species Anacardium occidentale, Croton heliotropiifolius, Croton sonderianus and Mimosa tenuiflora and their bioactivity on the immature phase of C. capitata. The specimens of the insects studied came from the breeding established within the Phytosanitary Clinic of the Center for Agrarian Social Human Sciences, from a population provided by the Invertebrate Laboratory of the Center for Agrarian Sciences, both at the Federal University of Paraíba. The plant material was obtained in areas of Caatinga in the state of Paraíba, Northeast Brazil. The following parameters were considered for the study: net yield (%) of plant extracts, ethanolic (Ethanol 90%) and hydroethanolic (Ethanol 70%), and the number of C. capitata insects emerged from the treated pupae. The extracts were obtained through dry extraction, through the technique of maceration of the plant tissue in a liquid medium of the extracting solvent and after filtering, to separate the liquid fraction from the solid, the extracts were concentrated with the removal of the solvent. The extracts were submitted to high performance liquid chromatography to determine the phenolic profile. Two bioassays were carried out in a completely randomized design, with a factorial scheme. A total of 10 pupae of C. capitata were distributed in five replications/treatment and subjected to direct contact with plant extracts (ethanolic and hydroethanolic), at different concentrations, for 60 seconds and the control treatment consisted of the absence of extracts. The hydroethanolic extracts of the studied plant species showed the highest net yields (%) when compared to the ethanolic extracts, highlighting the extracts of M. tenuiflora (27.76%) and A. occidentale (25.5%). indicating that 70% ethanol is an efficient extracting solvent in the process of obtaining bioextracts. In the biological activity assays, the ethanol extracts proved to be efficiently toxic to the insect, especially M. tenuiflora which, at all concentrations studied, caused the lowest mean emergence of adults of C. capitata, followed by the extract of A. occidentale, at concentrations of 150 μL/mL and 200 μL/mL and the mix (mixture of the 4 extracts), at concentrations of 100 μL/mL and 150 μL/mL. Regarding the hydroethanolic extracts, all four plant extracts showed bioactivity on the pupae, also highlighting the extracts of M. tenuiflora and A. occidentale, which showed lower averages of insects emerged from 100 μL/mL. Regarding the phenolic compounds present in the hydroethanolic extracts, 20 different phenolic compounds were identified, distributed differently among the four plant extracts, being common to all and in considerable amounts, Rutin and Myricetin. Thus, it can be concluded that the extracts of the botanical species A. occidentale, C. heliotropiifolius, C. sonderianus and M. tenuiflora are bioactive on Ceratitis capitata pupae, showing a potential bioinsecticidal property for this insect pest.